2016
DOI: 10.1021/acsami.6b01305
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Quantum Dot Surface-Engineered VO2Interwoven Nanowires: A Flexible Cathode Material for Lithium and Sodium Ion Batteries

Abstract: The use of electrode materials in their powdery form requires binders and conductive additives for the fabrication of the cells, which leads to unsatisfactory energy storage performance. Recently, a new strategy to design flexible, binder-, and additive-free three-dimensional electrodes with nanoscale surface engineering has been exploited in boosting the storage performance of electrode materials. In this paper, we design a new type of free-standing carbon quantum dot coated VO2 interwoven nanowires through a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
81
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(82 citation statements)
references
References 71 publications
1
81
0
Order By: Relevance
“…[37] For higher thermal and chemical stabilities, vanadium pentoxide (V 2 O 5 ) has been investigated as a cathode material for SIBs and supercapacitors. Early studies showed that V 2 O 5 aerogels can host reversible sodium insertion/extraction.…”
Section: Metal Oxides Mo Xmentioning
confidence: 99%
“…[37] For higher thermal and chemical stabilities, vanadium pentoxide (V 2 O 5 ) has been investigated as a cathode material for SIBs and supercapacitors. Early studies showed that V 2 O 5 aerogels can host reversible sodium insertion/extraction.…”
Section: Metal Oxides Mo Xmentioning
confidence: 99%
“…Recently, various active materials, such as FeS, [43] Na 2 FeP 2 O 7 , [44] Na 2 Ti 3 O 7 , [45] MoO 3−x , [46] NiCo 2 O 4 , [47] SnS 2 , [48] VO 2 , [49] FeFe(CN) 6 , [50] and Sb 2 X 3 (X = O, S), [51] have been directly grown or coated on the surface of carbon cloth. For example, Mo et al [47] reported the growth of three-dimensional porous NiCo 2 O 4 nanowire arrays on a carbon cloth (denoted as NCO@CFC) via the solution method with a subsequent annealing treatment (Figure 2e,f).…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 99%
“…Moreover, the flexible anode also showed improved cycling stability and rate performance compared with a NCO electrode prepared by the conventional slurry-casting method, suggesting that this flexible electrode is a promising candidate for flexible SIBs. Further, Balogun et al [49] synthesized VO 2 interwoven nanowires coated with carbon quantum dots (CQDs) grown on carbon cloth. When used as flexible cathode, it showed high sodium-storage capacity (320 mA h g −1 at 0.3C), good rate capacity (133 mA h g −1 at 60C), and high energy/power density (264 W h kg −1 /41 333 W kg −1 ), which are comparable to those for lithium-storage performance.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 99%
“…The energy and power densities of as-fabricated cathode for Na storage reach 264 Wh/kg and 41333 W/kg [30] VO 2 /rGO nanorods 160 mA h/g at 60 mA/g…”
Section: Vomentioning
confidence: 99%
“…Tong and co-workers also reported an unique free-standing cathode consisted of carbon quantum dots coated VO 2 nanowires. [30] The carbon quantum dots, which are flexible for surface engineering can efficiently ensure the integrity of nanowire. Another interesting work demonstrates the facile microwave-assisted solvothermal method to fabricate VO 2 (B)/ reduced graphene oxide (rGO) with good Na storage performance.…”
Section: Vomentioning
confidence: 99%